Control and Identification Toolbox (CIT): An Android application for teaching automatic control and system identification - Concha, Antonio (2019)
This article presents a free Android application, named as Control and Identification Toolbox (CIT), for teaching and learning the system response, automatic control, and the parameter identification of dynamic systems. The CIT app performs real‐time experiments and permits tuning a traditional proportional‐integral‐derivative controller, whose performance under constant or noise disturbances, introduced by the app, can be analyzed. Moreover, this app allows estimating the parameters of first‐ and second‐order linear systems by means of the recursive least squares method. The parameter estimates as well as the control system signals produced under common test input signals are displayed by the app. It runs in any Android device supporting a universal serial bus, which is connected with Arduino Uno or Mega boards that carry out data acquisition. Experimental results obtained using first‐ and second‐order low‐pass filters confirm the effectiveness of the proposed application. Moreover, undergraduate students evaluated the CIT app, and their responses are also presented.